A comparison of analytical methods to predict the bulk temperature in polymer spur gears. (July 2022) - Roda-Casanova, Victor; Fernandes, Carlos M.C.G.
Abstract: The mechanical properties of polymer gear transmissions are dependent on the operating temperature. Therefore, the prediction of the temperature of polymer gears is an important step during the design process. In this regard, analytical methods provide simple equations to predict the bulk temperature, but its applicability is limited by the underlying theory. In this work, a detailed background of the theoretical models that affect the temperature rise phenomena of polymer gears is provided. The methods suggested by Hachmann (and its implementation on VDI 2736 standard), Takanashi and Mao are derived from this common theoretical background. The common points, strengths and limitations of the methods are provided. The methods are illustrated with a variety of numerical examples and compared to reference experimental results. This comparison allowed us to draw some conclusions, to provide recommendations for the application of these methods, and identify potential measures of improving their results. Graphical abstract: Highlights: Review of theoretical models that rule the temperature rise phenomena of polymer gears. Hachmann, Takanashi and Mao methods are explained. The common points, strengths and limitations of these methods are identified. The methods are compared to reference experimental results.